Analysis of national human resource development (NHRD) policies of 2016 in South Korea with implications. Issue 4 (31st January 2020) - Roh, Kyungran; Ryu, Hyunok; McLean, Gary N.
Abstract : Purpose: The purpose of this study is to explore ways to improve the effectiveness and efficiency of national human resource development (NHRD) policies led by South Korean central government agencies, identifying what policy decisions have been made and how they were implemented. Design/methodology/approach: The authors collected data from the 2016 NHRD policy budget plans of the ministries and used content analysis. The unit of analysis was the fourth level, a sub-task, in each ministry's policy budget plan. All coded policy contents were analyzed in terms of the centralized NHRD model, as well as through the perspective of developmental task theory. Findings: The study yielded the following policy and implementation problems. First, the current system of NHRD policies established and implemented by individual ministries risks hampering the validity and effectiveness of the policies. Second, the structure of NHRD policy execution may cause similarity and redundancy across policies, thereby hindering the efficiency of the policies. Third, it is problematic when NHRD policies focus on solving short-term problems to the exclusion of long-term ones. Originality/value: This study provides public recommendations to improve the effectiveness and efficiency of NHRD policies created by South Korea's Central Government. If such an analysis has been made internally by the government, it has not been made publicly available. It also offers practical insights that might help to improve state-led human resource development policies for other countries – especially developing countries – that are planning to introduce central government-led NHRD or to improve existing NHRD policies.